The Effect of Push Up and Pull Up Exercises on Shooting Free Throw Results in Basketball Athletes in Jembrana Regency - Arya Tangkas Prasetya; Ketut Addy Indrawan; Ni Gusti Ayu Lia Rusmayani (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
A shooting free throw is a shot awarded to a player to score, as a result of being distracted by an opposing player in an attempt on a field shot. To master it, systematic training is needed, one of which is push-up and pull-up exercises. This study aims to determine the effect of push-up and pull-up exercises on the results of shooting free throws for basketball athletes in the Jembrana Regency. This research was carried out using a quasi-experimental research method with a pretest and post-test approach with a control group design. The population of this study was basketball athletes in the PERBASI Region, Jembrana Regency, with a sample of 30 athletes. Measurements were carried out during the pretest and post-test, and the push-up and pull-up exercise program was carried out 3 times a week, which was carried out for 5 weeks. The results showed that: 1) Push-up and pull-up exercises affected the results of shooting free throw scores for basketball athletes in Jembrana Regency. There is a difference in the results of shooting free throws for basketball athletes who are given push-up and pull-up exercises compared to ball athletes who are only given conventional training. From the results of this study, it means that push-up and pull-up exercises can increase free throw shooting scores by increasing the arm muscle strength of basketball athletes.